2006
DOI: 10.1682/jrrd.2005.08.1365
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver distress in parkinsonism

Abstract: Abstract-This study examined the frequency and degree of caregiver burden in persons with parkinsonism, a group of disorders with four primary symptoms that include tremor, rigidity, postural instability, and bradykinesia. We assessed associations between perceived caregiver burden and physical, cognitive, and functional impairments using well-established tools for persons with parkinsonism. The 49 individuals with parkinsonism ranged in age from 61 to 87 (mean = 75), while their caregivers (N = 49) ranged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
0
49
1
3
Order By: Relevance
“…Owing to both the motor and non-motor symptoms associated with the disease process, patients become increasingly reliant on formal and informal caregivers to assist with daily activities [14], a scenario that is closely associated with increasing caregiver distress [15] and transition to nursing home placement [16,17]. In 2011, 5% of permanent residents living in residential aged care facilities in Australia had a diagnosis of PD [18] and at $AUD236.0 million, aged care represented 59% of the health system costs for PD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to both the motor and non-motor symptoms associated with the disease process, patients become increasingly reliant on formal and informal caregivers to assist with daily activities [14], a scenario that is closely associated with increasing caregiver distress [15] and transition to nursing home placement [16,17]. In 2011, 5% of permanent residents living in residential aged care facilities in Australia had a diagnosis of PD [18] and at $AUD236.0 million, aged care represented 59% of the health system costs for PD [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, we are not aware of ADL scales with better psychometric properties in PDD. Nevertheless, the current analysis provides encouraging evidence that rivastigmine treatment may help some individuals maintain basic and higher level functioning in ADLs, and thereby improve the quality of life of patients and their caregivers [14,32] . Additional prospective studies are warranted in order to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…After a review of validated PD caregiving instruments [1,15,18,20] , the researchers found none that integrated all the required components for this study. The preferred survey was one devised for a mailed caregiver study, contained specific questions unique to this sample of participants, and was simple and short in design so that caregivers would be more likely to complete the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The relationships among the veterans and family members are affected early in the disease process and as the disease advances, the family caregivers increasingly assume a multitude of daily tasks that become as essential to the patient's well-being as other treatment methods [1][2][3] . Nurses relate to these PD caregivers on a regular basis and make assumptions about their stressors and needs often without the advantage of subjective information that would promote individualized care.…”
Section: Introductionmentioning
confidence: 99%